PENGEMBANGAN LKPD INTERAKTIF BERBANTUAN LIVEWORKSHEET PADA MATERI ANALISIS TEKS IKLAN SISWA KELAS VIII - Fuza Anggriana; Rosmaini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop interactive student worksheets (LKPD) using the Liveworksheet platform for teaching advertisement text analysis to eighth-grade students. The research is grounded in several issues identified in classroom practice, including limited variation in existing worksheets, low student engagement, and the underutilization of digital technology in learning activities. This study employed a research and development (R&D) approach adapted from the Borg and Gall model, simplified into five stages: needs analysis, data collection, product design, validation, and revision. The subjects consisted of 32 students, one Indonesian language teacher, and two expert validators (material and media experts). Data were gathered through questionnaires, interviews, and validation sheets, and analyzed using qualitative and quantitative techniques with a Likert scale. The results indicate that the developed LKPD is categorized as highly feasible, achieving a validation score of 100% from the material expert and 95% from the media expert, with an overall average of 97.5%. The product demonstrates strong potential to enhance students’ motivation, participation, and analytical skills in understanding advertisement texts through interactive and technology-based learning media.